Trade shocks, labor markets and elections in the first globalization - Richard Bräuer; Wolf-Fabian Hungerland; Felix Kersting (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2021)
This paper studies the economic and political effects of a large trade shock in agriculture - the grain invasion from the Americas - in Prussia during the first globalization (1871-1913). We show that this shock accelerated the structural change in the Prussian economy through migration of workers to booming cities. In contrast to studies using today's data, we do not observe declining per capita income, health outcomes or political polarization in counties aected by foreign competition. Our results suggest that the negative and persistent eects of trade shocks we see today are not a universal feature of globalization, but depend on labor mobility. For our analysis, we digitize data from Prussian industrial and agricultural censuses on the county level and combine it with national trade data at the product level. We exploit the cross-regional variation in cultivated crops within Prussia and instrument with Italian trade data to isolate exogenous variation.
Keywords: F14; F16; F66; F68; N13; R12; 330; Globalization; import competition; labor market; agriculture; migration; trade shock; elections; Germany; Prussia